Prediction of Difficult Laryngoscopy Using Ultrasound: A Systematic Review and Meta-Analysis. Issue 1 (3rd November 2022) - Bhargava, Vidit; Rockwell, Nicholas A.; Tawfik, Daniel; Haileselassie, Bereketeab; Petrisor, Cristina; Su, Erik
Abstract : OBJECTIVES: Evaluate associations between ultrasound measures and difficult laryngoscopy. DATA SOURCES: MEDLINE, Embase, Google Scholar, Web of Science, and the Cochrane Library were searched using MeSH terms and keywords. STUDY SELECTION: Studies published in English describing the use of airway ultrasound for identifying difficult laryngoscopy, with sufficient data to calculate sensitivity and specificity using 2 × 2 tables. DATA EXTRACTION: We assigned the described indices of airway dimension to one of three domains based on methodology characteristics: anterior tissue thickness domain, anatomical position domain, and oral space domain. We then performed a bivariate random-effects meta-analysis, deriving pooled sensitivity, specificity, diagnostic odds ratio, positive likelihood ratio, and negative likelihood ratio estimates. We assessed risks of bias using Quality Assessment of Diagnostic Accuracy Studies-2 analysis. DATA SYNTHESIS: Thirty-three studies evaluating 27 unique indices were included in the meta-analysis. The ultrasound protocols of the included studies were heterogeneous. Anterior tissue thickness demonstrated a pooled sensitivity of 76% (95% CI, 71–81%), specificity of 77% (95% CI, 72–81%), and an area under the receiver operating characteristic curve (AUROC) of 0.83 (95% CI, 0.80–0.86). Anatomical position demonstrated a pooled sensitivity of 74% (95% CI, 61–84%), specificity of 86% (95% CI, 78–91%), and an AUROC of 0.87 (95% CI, 0.84–0.90). Oral space demonstrated a pooled sensitivity of 53% (95% CI, 0.36–0.69), specificity of 77% (95% CI, 0.67–0.85), and an AUROC of 0.73 (95% CI, 0.69–0.77). CONCLUSIONS: Airway ultrasound metrics associate with difficult laryngoscopy in three domains: anterior tissue thickness, anatomic position, and oral space. An assessment instrument combining clinical and ultrasound assessments may be an accurate screening tool for difficult laryngoscopy.